1982
DOI: 10.3181/00379727-169-41310
|View full text |Cite
|
Sign up to set email alerts
|

Rat Strain Differences in Gluconeogenesis by Isolated Hepatocytes

Abstract: An investigation of the glucose production by isolated hepatocytes from lipemic BHE and nonlipemic Wistar rats was conducted. Hepatocytes were isolated from 40-hr starved young rats. Glucose, P-hydroxybutyrate, and acetoacetate production and ATP content of the cells after 60 min incubation with a variety of substrates were determined. BHE hepatocytes produced more glucose and /3-hydroxybutyrate than Wistar hepatocytes. No strain differences in ATP content were observed. It is suggested that, in part, the hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…This observation was expected; however, they also reported an increase in fatty acid oxidation. The latter observation is consistent with our finding of a tenfold elevation in serum free glycerol, a product of peripheral tissue lipolysis, and an increase in hepatic glycerol use for glucose synthesis and fatty acid reesterification (Berdanier et al, 1978(Berdanier et al, , 1982. Detailed studies of frozen-clamped hepatic tissue from stock-dietfed rats, (a process in which large clamps, immersed in liquid nitrogen, smash the excised liver to the thinness of a potato chip) revealed that liver cells had elevated phosphorylation and redox states, findings consistent with elevated rates of hepatic lipogenesis (Berdanier et al, 1979).…”
Section: Early Phenotype Detectionsupporting
confidence: 90%
See 1 more Smart Citation
“…This observation was expected; however, they also reported an increase in fatty acid oxidation. The latter observation is consistent with our finding of a tenfold elevation in serum free glycerol, a product of peripheral tissue lipolysis, and an increase in hepatic glycerol use for glucose synthesis and fatty acid reesterification (Berdanier et al, 1978(Berdanier et al, , 1982. Detailed studies of frozen-clamped hepatic tissue from stock-dietfed rats, (a process in which large clamps, immersed in liquid nitrogen, smash the excised liver to the thinness of a potato chip) revealed that liver cells had elevated phosphorylation and redox states, findings consistent with elevated rates of hepatic lipogenesis (Berdanier et al, 1979).…”
Section: Early Phenotype Detectionsupporting
confidence: 90%
“…As mentioned previously, gluconeogenesis by isolated hepatocytes from rats starved for 40 hours is 20 percent greater in BHE rats than in WI or SD rats fed a stock diet ad libitum (Berdanier, 1982). Gluconeogenesis can be increased by feeding a 65 percent sucrose diet (Park et al, 1983(Park et al, , 1986 and increased even further by substituting hydrogenated coconut oil for corn oil in the sucrose diet .…”
Section: Early Phenotype Detectionmentioning
confidence: 93%
“…One factor that could have affected our assessments of retinol status was the well-known strain difference in liver fat due to both an increase in de novo fatty acid synthesis and fatty acid mobilization. BHE/Cdb rats have twice the rate of fatty acid synthesis and 10 times more lipolysis than normal rats (6)(7)(8). In the presence of increased fatty acids, retinol is preferentially converted to retinyl esters instead of retinal and retinoic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The BHE/Cdb rat is an animal model of mitochondrial diabetes with a maternally inherited mutation in the mitochondrially encoded ATPase 6 gene (1,2). Like humans with mitochondrial diabetes (3), young rats have hyperinsulinemia (4), insulin resistance (5), increased hepatic lipogenesis (6), increased gluco-neogenic capacity (7), and increased ketogenesis (7,8). As the rat ages, glucose-stimulated insulin secretion decreases (4,9), and, with age, impaired glucose tolerance develops (8).…”
Section: Introductionmentioning
confidence: 99%
“…Among these were: a two-fold increase in hepatic de novo fatty acid and cholesterol synthesis (1 12) and lipolysis (113), a 40% increase in gluconeogenesis (114), and a 20% reduction in ATP synthesis efficiency (115). In an experiment by Fowler and Berdanier (1 16), Sprague-Dawley rats were fed a sucrose-rich diet that contained 0.02% 3-(3,4-dichlorophenyl)-1,1 -dimethylurea (DCMU), a mild OXPHOS uncoupling agent.…”
Section: The Bhe/cdb Rat: a Rat With Mtdna Mutation In The Atp 6 Genementioning
confidence: 99%